Az 1983. évi Codex Iuris Canonici házasságok érvénytelenségét kinyilvánító peres eljárásainak gyakori jogcímei a kortárs bírósági gyakorlat fényében - Völgyesi, Levente (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
This study reports on the matrimonial litigation proceedings of contemporary cases. Standing based on the method of legal comparison, it is possible to investigate the substantive matrimonial law of a sovereign legal system, primarily from the aspect of practice. The author primarily wishes to share his own practical experiences with the professional reader. The reform of the Codex Iuris Canonici is based on the theological reform of the Second Vatican Council, which placed pastoral aspects before jurisprudential aspects, thus the resulting Code (1983) also looks at the institution of marriage through the lens of a love relationship, not denying the contractual nature, but not emphasizing it either. Nowadays, most court proceedings are typically run on three legal grounds, so the study is limited to describing them. The presentation relies on three sources: the judgments of a local ecclesiastical court, canonical publications, and the opinions of the Rota Romana.